On the Influence of Piecewise Defined Contact Geometries on Friction Dampers - Aramendiz Fuentes, Jimmy Alberto (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2023)
This work considers dampers that do not solely focus on a single strategy but instead combine them. The capabilities of conventional dry friction dampers are expanded by taking into account piecewise defined contact geometries. This leads to friction dampers that change their behavior depending on the amplitude of the oscillations. The vibration damping device in this work, introduces damping at high oscillation amplitudes and takes advantage of absorption at low oscillation amplitudes.